Agravos agudos de saúde de prematuros moderados e tardios no primeiro mês de vida - Rosa, Natana Pereira (2018)
Gestational age at birth is an intervening factor in the development of health problems, especially in the neonatal period. The birth of a premature infant with gestational age of 32 to 37 incomplete weeks may not imply immediate health complications, however, little is known about the development of health problems during the first 28 days of life of this population. Thus, the objective of the study was to analyze the development of acute health problems in moderate (GA 32 weeks of age completed at 33 weeks and 6 days) and late (GA 34 weeks up to 36 weeks and 6 days) in the first month of life. For that, a cross-sectional / epidemiological study was developed with a quantitative approach. Participants were 151 moderated and late preterm infants selected at a referral hospital for risk gestation in southern Brazil. The obstetric, neonatal, and socioeconomic data were collected through an instrument at the time of hospital admission. Data on the development of acute health problems were collected at the end of the first month of life via telephone contact. The analysis was performed using the SPSS program, version 20.0, with frequency comparison between the variables, using p <5% for statistical significance of the analysis. The ethical precepts were respected with the approval of the Ethics Committee in Research of the institution under number 1.511.201. The results showed that approximately 96.7% of premature infants developed at least one acute health condition, with vomiting being the most frequent. The development of acute respiratory health problems in the neonatal period showed a significant association with birth weight, Apgar 1 min <7 and Apgar 5 min <7, neonatal resuscitation need, place of hospitalization, type of diet, besides associations with the socioeconomic characteristics of the patients. It was concluded that the vomiting, cough and nauseated conditions were the most frequent in the Moderate and Late Prematurity in the neonatal period. In addition, there were significant associations between obstetric, neonatal and socioeconomic factors associated with a higher respiratory risk. The results found point to an attentive look at the group studied, as well as the need for follow-up of these newborns in the post-hospital discharge in a systematized manner.